2015
DOI: 10.1016/j.cmi.2015.07.018
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic characterization of Central/Southern European lineage 2 West Nile virus: analysis of human outbreaks in Italy and Greece, 2013–2014

Abstract: In recent years, West Nile virus (WNV) lineage 2 has been spreading and causing disease outbreaks in humans and animals in Europe. In order to characterize viral diversity, we performed full-length genome sequencing of WNV lineage 2 from human samples collected during outbreaks in Italy and Greece in 2013 and 2014. Phylogenetic analysis showed that these WNV lineage 2 genomes belonged to a monophyletic clade derived from a single introduction into Europe of the prototype Hungarian strain. Correlation of phylog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
54
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(57 citation statements)
references
References 35 publications
2
54
0
1
Order By: Relevance
“…Various strains of WNV lineage 1 (the Western Mediterranean clade) have been involved in human infection in Italy since 1998, whereas WNV lineage 2 was documented for the first time in 2011 [18–20]. However, it has since spread throughout the country and is now the most frequently identified lineage in Italy [19, 21, 22]. …”
Section: Introductionmentioning
confidence: 99%
“…Various strains of WNV lineage 1 (the Western Mediterranean clade) have been involved in human infection in Italy since 1998, whereas WNV lineage 2 was documented for the first time in 2011 [18–20]. However, it has since spread throughout the country and is now the most frequently identified lineage in Italy [19, 21, 22]. …”
Section: Introductionmentioning
confidence: 99%
“…More recently, however, outbreaks involving lineage 2 WNV strains have caused human disease and death in Greece, Italy, Romania, Russia, and, potentially, South Africa. (Barzon et al, 2015; McMullen et al, 2013; Papa et al, 2011; Platonov et al, 2011; Sirbu et al, 2011; Venter and Swanepoel, 2010; Zaayman and Venter, 2012)…”
Section: Introductionmentioning
confidence: 99%
“…KU206781). Phylogenetic analysis showed that the virus belonged to the Central/Southern-European WNV lineage 2 clade and the Greek cluster ( 6 ). Sequence showed high similarity with Greece Nea Santa 2010 and Hungary/578 strains (99.66% and 99.57% nt identity, respectively), which suggested that the virus probably had a common ancestor with Greek strains.…”
mentioning
confidence: 99%
“…Accordingly, analysis of the polyprotein identified amino acid substitutions that are typically found in WNV strains from Greece (i.e., NS2B V119I, NS3 H249P, NS4B S14G/T49A/V113M) ( 6 ) and unique mutations not present in other strains (i.e., E I159M, T436A, NS1 K92N, NS4B N220D, NS5 D141G). These results indicate that the virus might have evolved independently before its emergence in Bulgaria.…”
mentioning
confidence: 99%
See 1 more Smart Citation